Dinamika Keterlibatan Stakeholders Pada Perencanaan Strategi Pemasaran Sosial di Smile Train Indonesia (UI Scholars Hub, 2018)
This research discusses the dynamics, obstacles, and challenges that occur in the stage of social marketing strategy planning process undertaken by the management of Smile Train Indonesia with the organizational stakeholders as well as the efforts made by the organization management to overcome those. This research is a qualitative research with descriptive design. The results conclude that there is rarely conflicts between organizations and stakeholders in the organization’s social marketing planning process because of good conflict management and collaboration. But acknowledged by the stakeholders, there are several obstacles and challenges that are faced during the planning process. This research suggests that organizational management should improve the social market marketing research effort to prevent and overcome the dynamics, obstacles, and challenges that occur in the social marketing planning process